EKSPLORASI NILAI FABEL SEBAGAI SARANA ALTERNATIF EDUKASI SISWA - Juanda, Juanda (Universitas Pendidikan Indonesia, 2019)
Children’s character must be built since their early age. Children should be educated and habituated with good characters so that good character will be embedded until they are grown up. A diversity of fables can be used as a medium to build the children's character. The goal in this research is exploration character educational values which are contained in the fable “Kisah Sahabat Rimba” by Yosep Rustandi. The research method uses qualitative descriptive with content analisys to describe the characters in fable “Kisah Sahabat Rimba” by Yosep Rustandi. The result of the research, it was known that there are some universal characters which can be exemplified from the fables “Kisah Sahabat Rimba” by Yosep Rustandi such as thorough, politeness, humble, honest, and respectful.